2010
DOI: 10.1128/iai.01377-09
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular Passage of Neisseria meningitidis across a Polarized Respiratory Epithelium

Abstract: Neisseria meningitidis is a major cause of sepsis and meningitis but is also a common commensal, present in the nasopharynx of between 8 and 20% of healthy individuals. During carriage, the bacterium is found on the surface of the nasopharyngeal epithelium and in deeper tissues, while to develop disease the meningococcus must spread across the respiratory epithelium and enter the systemic circulation. Therefore, investigating the pathways by which N. meningitidis crosses the epithelial barrier is relevant for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 77 publications
(91 reference statements)
2
50
0
Order By: Relevance
“…On the other hand, there is no visible opening of tight-junction-forming epithelial monolayers of T84 or Caco2 cells. Our data are consistent with previously published works showing that the crossing of a tight-junction-forming epithelial monolayer occur via a transcytosis pathway and is not associated with a decrease in transepithelial resistance or a disruption of intercellular junctions (18,23,31). This is consistent with the low frequency of infection, although the opening of the endothelial wall seems to be very efficient and can participate in the peripheral symptoms observed in meningococcal infections.…”
Section: Figsupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, there is no visible opening of tight-junction-forming epithelial monolayers of T84 or Caco2 cells. Our data are consistent with previously published works showing that the crossing of a tight-junction-forming epithelial monolayer occur via a transcytosis pathway and is not associated with a decrease in transepithelial resistance or a disruption of intercellular junctions (18,23,31). This is consistent with the low frequency of infection, although the opening of the endothelial wall seems to be very efficient and can participate in the peripheral symptoms observed in meningococcal infections.…”
Section: Figsupporting
confidence: 82%
“…Meningococcal interaction on epithelial cells is responsible as for endothelial cells for the formation of cortical plaque with accumulation under the colony of ezrin, actin, adhesion molecules and membrane receptors that are clustered in a honeycomb-like structure. However, previous reports obtained with capsulated and piliated N. meningitidis suggested that tight junctions were not altered by meningococcal interaction with epithelial cells and that bacteria were likely to cross epithelial monolayer using the transcellular route (23,31). We subsequently aimed at deciphering the discrepancies observed in meningococcal host cell interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that bacteria can transcytose across cultured cell monolayers, including Campylobacter jejuni (Grant et al, 1993;Russell and Blake, 1994;Bacon et al, 2001;Kopecko et al, 2001;Hu et al, 2008;Watson and Galán, 2008), Neisseria gonorrhoeae and Neisseria meningitidis (Makino et al, 1991;Merz and So, 2000;Kuespert et al, 2006;Wang et al, 2008;Sutherland et al, 2010), Streptococcus pneumoniae (Zhang et al, 2000;Kaetzel, 2001), and Escherichia coli (Burns et al, 2001;Xie et al, 2004). Yet, with the exception of bacterial sampling by M cells (see next paragraph), this is the first time to our knowledge that a bacterium has been shown to translocate across an epithelial layer by transcytosis in vivo, resulting in its systemic dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…, pharmacological compounds [2][3][4][5][6] , and bacterial [7][8][9] and viral pathogens, including influenza virus, rhinovirus and severe acute respiratory syndrome -associated coronavirus [10][11][12][13][14] . Recently, we demonstrated that Calu-3 cells are susceptible to respiratory syncytial virus (RSV) infection in a manner consistent with NHBE 15,16 .…”
mentioning
confidence: 99%